2014
DOI: 10.1007/s00415-014-7502-9
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, open-label, follow-on study to assess the long-term maintenance of effect, tolerance and safety of THC/CBD oromucosal spray in the management of neuropathic pain

Abstract: Peripheral neuropathic pain (PNP) poses a significant clinical challenge. The long-term efficacy of delta-9-tetrahydrocannabinol (THC)/cannabidiol (CBD) oromucosal spray was investigated in this 38-week open-label extension study. In total, 380 patients with PNP associated with diabetes or allodynia entered this study from two parent randomised, controlled trials. Patients received THC/CBD spray for a further 38 weeks in addition to their current analgesic therapy. Neuropathic pain severity was the primary eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 31 publications
1
58
0
1
Order By: Relevance
“…Randomized clinical trials of THC:CBD oromucosal spray (nabiximols) for the treatment of chronic neuropathic pain conditions are summarized in Table 2. [87][88][89][90][92][93][94][95][96][97][98] THC:CBD oromucosal spray (nabiximols) has shown mainly positive results in studies of patients with MSassociated neuropathic pain ( Table 2). [87][88][89][90] A placebo-controlled RCT of patients with central neuropathic pain due to MS reported a near 2-fold higher mean change from baseline on the 0-10 pain NRS (-2.7 vs -1.4; p = 0.005) during 4 weeks' treatment with THC:CBD oromucosal spray (nabiximols) or placebo as adjunctive analgesia.…”
Section: Treatment Of Chronic Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized clinical trials of THC:CBD oromucosal spray (nabiximols) for the treatment of chronic neuropathic pain conditions are summarized in Table 2. [87][88][89][90][92][93][94][95][96][97][98] THC:CBD oromucosal spray (nabiximols) has shown mainly positive results in studies of patients with MSassociated neuropathic pain ( Table 2). [87][88][89][90] A placebo-controlled RCT of patients with central neuropathic pain due to MS reported a near 2-fold higher mean change from baseline on the 0-10 pain NRS (-2.7 vs -1.4; p = 0.005) during 4 weeks' treatment with THC:CBD oromucosal spray (nabiximols) or placebo as adjunctive analgesia.…”
Section: Treatment Of Chronic Neuropathic Painmentioning
confidence: 99%
“…91 The results of studies of THC:CBD spray (nabiximols) in patients with neuropathic pain of origins other than MS are mixed ( Table 2). [92][93][94][95][96][97][98] A RCT registered at ClinicalTrials.gov which compared THC:CBD spray (nabiximols) and placebo for relief of intractable neuropathic pain associated with spinal cord injury found no difference between treatments for change from baseline in pain 0-10 NRS scores (-0.74 vs -0.69; p = 0.71) after 3 weeks' treatment (ClinicalTrials.gov identifier NCT01606202). 92 In a study of central neuropathic pain due to brachial plexus avulsion, the difference in the mean pain severity score during the last 7 days of treatment with THC:CBD oromucosal spray (nabiximols) was statistically significant (p = 0.005) compared with placebo, although failed to satisfy the a priori assumed level for clinical significance.…”
Section: Treatment Of Chronic Neuropathic Painmentioning
confidence: 99%
“…RCTs involving cannabinoids and cannabis have demonstrated effective analgesia in various patient populations with chronic neuropathic pain refractory to other treatments [155][156][157][158][159][160][161] (see Table S1 online). Due to changes in the legalization of cannabis and the growing use of medical cannabis for chronic pain syndromes, it is important to consider cannabinoid medicine as part of an integrative medicine approach.…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Clinical trials investigating various indications showed long-term effects of cannabis-based medicine. These studies lasting from 38 weeks to 3.5 years showed no major safety concerns and a generally good tolerability [9-16]. Nevertheless, the medical use of cannabis is controversially discussed.…”
Section: Introductionmentioning
confidence: 99%